Angiogenesis Inhibition by a Short 13 Amino Acid Peptide Sequence of Tetrastatin, the α4(IV) NC1 Domain of Collagen IV - Vautrin-Glabik, Alexia; Devy, Jérôme; Bour, Camille; Baud, Stéphanie; Choulier, Laurence; Hoarau, Anthony; Dupont-Deshorgue, Aurélie; Sellier, Christèle; Brassart, Bertrand; Oudart, Jean-Baptiste; Ramont, Laurent; Monboisse, Jean Claude; et al. (Frontiers in Cell and Developmental Biology, 2020)
Angiogenesis is defined as the formation of new capillaries by sprouting from the pre-existing microvasculature. It occurs in physiological and pathological processes particularly in tumor growth and metastasis. α1, α2, α3, and α6 NC1 domains from type IV collagen were reported to inhibit tumor angiogenesis. We previously demonstrated that the α4 NC1 domain from type IV collagen, named Tetrastatin, inhibited tumor growth in a mouse melanoma model. The inhibitory activity was located in a 13 amino acid sequence named QS-13. In the present paper, we demonstrate that QS-13 decreases VEGF-induced-angiogenesis in vivo using the Matrigel plug model. Fluorescence molecular tomography allows the measurement of a 65% decrease in Matrigel plug angiogenesis following QS-13 administration. The results are confirmed by CD31 microvessel density analysis on Matrigel plug slices. QS-13 peptide decreases HUVEC migration and pseudo-tube formation in vitro. Relevant QS-13 conformations were obtained from molecular dynamics simulations and docking. A putative interaction of QS-13 with α5β1 integrin was investigated. The interaction was confirmed by affinity chromatography, solid phase assay and surface plasmon resonance. QS-13 binding site on α5β1 integrin is located in close vicinity to the RGD binding site, as demonstrated by competition assays. Collectively, our results suggest that QS-13 exhibits a mighty anti-angiogenic activity that could be used in cancer treatment and other pathologies with excessive angiogenesis such as hemangioma, psoriasis or diabetes.